2015
DOI: 10.3906/bot-1407-1
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Russula (Russulaceae) from India based on morphological and molecular (ITS sequence) data

Abstract: Russula kanadii (Russulaceae, Basidiomycota) is described as a new species from West Bengal, India, and is assigned to the subgenus Heterophyllidia, section Heterophyllae, and subsection Virescentinae. A comprehensive description, photographs, and comparisons with morphologically similar and phylogenetically related species are provided. Inferences of its phylogenetic relationships within the genus are provided based on the sequence of the nuclear internal transcribed spacer (ITS) region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 16 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Ilicinae (BP 100, PP 1.00) on the one side, and the remaining subsections of Rigidae (PP 0.87, BP 77) on the other, including subsections Griseinae (divided in two clades, those of / R. ochrospora and / R. grisea ), Virescentinae , Pseudoepitheliosinae , Heterophyllae and Amoeninae . Most of these clades were also significantly supported by the phylogenetic reconstructions of Rigidae conducted by Dutta et al (2015) and Zhao et al (2015). The only European sequestrate species related to sect.…”
Section: Resultsmentioning
confidence: 57%
“…Ilicinae (BP 100, PP 1.00) on the one side, and the remaining subsections of Rigidae (PP 0.87, BP 77) on the other, including subsections Griseinae (divided in two clades, those of / R. ochrospora and / R. grisea ), Virescentinae , Pseudoepitheliosinae , Heterophyllae and Amoeninae . Most of these clades were also significantly supported by the phylogenetic reconstructions of Rigidae conducted by Dutta et al (2015) and Zhao et al (2015). The only European sequestrate species related to sect.…”
Section: Resultsmentioning
confidence: 57%
“…8 In search of wild edible mushrooms (WEM) that are commonly prized by the local forest dwellers across the country, we came across quite a number of mushroom taxa that has been previously identified and reported therein. 3,9,10 Ramaria subalpina K. Das & K. Acharya [commonly called as 'thokrechyau' (Nepali; 'thokre' = in bunch and 'chyau' = mushroom)], a newly described taxa, 10 traditionally consumed as an edible mushroom ( Figure 1A) by the ethnic people of subalpine Sikkim Himalaya for its flavor, texture and gastronomic delicacy since time immemorial was explored to understand its antioxidative potentiality and bioactive constituents.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, several investigators demonstrated that using both morphological and molecular evidence provides valuable features for species delimitation (Duminil et al, 2012;Farsi et al, 2013;Vaezi et al, 2014;Dutta et al, 2015;Korkmaz et al, 2015;Xu et al, 2015). The purpose of this study was to describe and illustrate Phlomis iranica as a new species using a combination of morphological and molecular datasets.…”
mentioning
confidence: 99%